The Influence of Ease of Transactions using ShopeePay, Promotion and Hedonism Lifestyle on Consumptive Behavior of Accounting Education Students Muhammadiyah University Surakarta - Aprilliyanti, Riska Sendy; Asmawan, Moh. Chairil (Proceedings International Conference on Education Innovation and Social Science, 2023)
Purpose ofthis reseach: (1) the effect of the ease of transactions using shopeepay on student consumptive behavior. (2) the effect of promotion on student consumptive behavior. (3) the influence of hedonism lifestyle on consumptive behavior. (4) the joint effect of the ease of transactions using shopeepay, promotions, and hedonism lifestyle on student consumptive behavior. This type of research uses quantitative research with a correlation research design. Population used Accounting Education Students in semester 1 to semester 7 with a total of 374 students. The samples were 177 students based on the Issac and Michael tables using the random sampling. Data collection techniques using online questionnaires google form with data analysis techniques multiple linear regression analysis. The results obtained are: 1) The ease of transactions using Shopeepay has no effect on student consumptive behavior. Based on the t test value 0,905 0,05 with an effective contribution of 1,4%. 2) Promotion has an effect on student consumptive behavior. Based on t test 2,383 > t table 1,973. A significance value of ,018 <0,05 with an effective contribution of 6,78%. 3) The hedonism lifestyle influences student consumptive behavior. Based on t test 5,534 > t table 1.973. A significance value of 0,000 <0,05 with an effective contribution of 19.15%. 4) The ease of transactions using shopeepay, promotions and hedonism lifestyles together influence student consumptive behavior. Based on the results of the significance F test with an F table value of 2.66. With a calculated F value of21,784. So that the independent variable affects the dependent variable. The coefficient of determination (R2) is 27,4%.